2022
DOI: 10.2147/ijgm.s364029
|View full text |Cite
|
Sign up to set email alerts
|

MMP2 Polymorphisms and Colorectal Cancer Susceptibility in a Chinese Han Population

Abstract: Colorectal cancer (CRC) is among the most common cancers worldwide and an important cause of cancer-related death. Inherited genetic variation plays a vital role in the occurrence and development of CRC. The aim of this study was to evaluate the association of single nucleotide polymorphisms (SNPs) in MMP2 with CRC risk. Patients and Methods: Three candidates, MMP2 SNPs, rs1053605, rs243849, and rs14070, were selected and genotyped using the Agena MassARRAY RS1000 system, and their association with risk of CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases known for their involvement in cancer prognosis [53] and have been widely explored for drug delivery and imaging [54]. According to a clinical statistical trial in a Chinese population, MMP variants are potential genetic markers for CRC risk [55]. Rashidzadeh et al [56] prepared enzyme-responsive hydrogels containing methotrexate (MTX) and chloroquine (CQ) in polymethylmethacrylic acid (PMAA), catalyzing the drug release in the presence of proteolytic enzymes.…”
Section: Enzyme-responsive Oral Nano-formulationsmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases known for their involvement in cancer prognosis [53] and have been widely explored for drug delivery and imaging [54]. According to a clinical statistical trial in a Chinese population, MMP variants are potential genetic markers for CRC risk [55]. Rashidzadeh et al [56] prepared enzyme-responsive hydrogels containing methotrexate (MTX) and chloroquine (CQ) in polymethylmethacrylic acid (PMAA), catalyzing the drug release in the presence of proteolytic enzymes.…”
Section: Enzyme-responsive Oral Nano-formulationsmentioning
confidence: 99%
“…CRC is a multifactorial disease involving genetic, environmental and lifestyle risk factors ( 103 ). The high heritability and frequent recurrence of CRC leads to considerable mortality and the association with poor prognosis ( 104 ). At 2020, there were >1.9 million new cases of CRC (including anal) and nearly 935,000 mortalities in worldwide ( 105 ).…”
Section: Relationship Between Cct and Crcmentioning
confidence: 99%
“…Makar et al demonstrated that the rs20417 polymorphism in the cyclooxygenase 2 ( COX-2 ) gene is associated with a higher risk of rectal cancer [ 5 ]. Conversely, Liu et al showed that polymorphism rs24384 in the matrix metallopeptidase 2 ( MMP2 ) gene is associated with a decreased risk of rectal cancer [ 6 ]. Similarly, other polymorphisms that are related to decreased risk of rectal cancer are in the methylenetetrahydrofolate reductase ( MTHFR ) gene (rs1801133) [ 7 ] and the peroxisome proliferators-activated receptor gamma ( PPARγ ) gene (rs1801282) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%